The effect of agritourism experience on consumers' future food purchase patterns. (February 2019) - Kim, Sumin; Lee, Seul Ki; Lee, Dongmin; Jeong, Jaeseok; Moon, Junghoon
Abstract: Recent studies on agritourism share a common voice in that the economic benefit of agritourism to farms is significant but rather small. However, the majority of studies examine only the short-term economic impact of agritourism. This suggests that the potential long-run economic impacts of agritourism may not have been empirically investigated yet, leading to underestimation of its net impact. Meanwhile, theories on mere exposure and product familiarity suggest that agritourism may lead tourists to change their agriproduct purchasing patterns after the experience. Thus, this study examines the effect of agritourism experience on consumers' future grocery purchase patterns. Household-level consumer panel data on grocery expenditure is estimated through the Almost Ideal Demand System (AIDS) approach. The results indicate that agritourism experience significantly alters consumers' expenditure patterns in the food categories of grain, vegetable, fruit, meat, and fish. Implications for research and practice are discussed along with the findings of the study. Highlights: Economic impact of agritourism is often considered significant but small. Mere exposure and product familiarity theories suggest the possibility of a long-term economic impact from agritourism. This study investigates the prolonged economic impact of agritourism from post hoc grocery consumption of agritourists. Almost ideal demand system is estimated on food expenditure data after agritourism. Agritourism significantly influences tourists' future food purchase patterns.